Introducing Adobe Photoshop Software Tools among Secondary School Multimedia Students by Using Augmented Reality - Intang, Ezra; Ahmad Zaki, Nadia Akma; Yani, Achmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Aplikasi ini memperkenalkan tools perisian Adobe Photoshop dalam kalangan pelajar Multimedia, yang dibangunkan adalah bertujuan untuk membantu pelajar Multimedia untuk mengenali tools perisian Adobe Photoshop dengan cara yang lebih moden iaitu menggunakan AR. Reka bentuk aplikasi ini dibangunkan dengan menggunakan elemen multimedia seperti audio, video, grafik, animasi dan teks. Kajian ini dijalankan bagi mengetahui persepsi pengguna yang ianya merangkumi kebolehgunaan, keberkesanan dan reka bentuk responden terhadap hasil produk akhir yang telah dibangunkan. Pembangunan aplikasi ini dibangunkan menggunakan ADDIE Model. Dapatan kajian menunjukkan min yang terkumpul bagi responden kajian ialah 3.50 bagi persepsi kebolehgunaan, 3.33 bagi min persepsi keberkesanan dan 3.57 bagi persepsi reka bentuk aplikasi. Secara keseluruhannya, hasil kajian yang diperolehi oleh responden kajian menunjukkan skor min yang tinggi. Introducing Adobe Photoshop Software Tools among Secondary School Multimedia Students by Using Augmented Reality Abstract: This application is introducing Adobe Photoshop software tools among multimedia students; it was developed to help multimedia students to recognize Adobe Photoshop software tools in a more modern way that is using AR. The design of this application is developed using multimedia elements such as audio, video, graphics, animation, and text. This study was conducted to find out consumer perceptions which include the usability, effectiveness, and design of respondents to the final product that has been developed. The development of this application was developed using the ADDIE Model. The findings of the study showed that the cumulative mean for the study respondents was 3.50 for the perception of usability, 3.33 for the mean of the perception of effectiveness, and 3.57 for the perception of application design. Overall, the results obtained by the study respondents showed a high mean score. Keywords: ADDIE, Adobe Photoshop, Augmented Reality, Teaching and Learning Aids.